AB0448 SAFETY AND EFFICACY OF FILGOTINIB IN JAPANESE PATIENTS ENROLLED IN A GLOBAL PHASE 3 TRIAL OF PATIENTS WITH ACTIVE RHEUMATOID ARTHRITIS AND INADEQUATE RESPONSE OR INTOLERANCE TO BIOLOGIC DMARDS. (June 2019) - Takeuchi, Tsutomu; Matsubara, Tsukasa; Atsumi, Tatsuya; Amano, Koichi; Ishiguro, Naoki; Sugiyama, Eiji; Yamaoka, Kunihiro; Genovese, Mark C.; Kalunian, Kenneth; Walker, David; Gottenberg, Jacques-Eric; Vlam, Kurt de; et al.
Abstract : Background: Filgotinib (FIL), an oral, selective inhibitor of Janus kinase 1 (JAK1), has demonstrated efficacy in a phase 3 study in bDMARD-IR patients with active rheumatoid arthritis (RA). Objectives: We report results of Japanese patients enrolled in the FINCH2 study (ClinicalTrials.gov Identifier: NCT02873936 ) of FIL in patients with RA and an inadequate response or intolerance to ≥1 bDMARDs. Methods: FINCH2 (ClinicalTrials.gov: NCT02873936 ) was a 24-week, randomized, placebo-controlled, phase 3 trial conducted globally at 114 sites, including at sites in Japan, from July 2016–June 2018. Male and female adults with moderately-to-severely active RA and inadequate response/intolerance to ≥1 prior bDMARDs were randomized 1:1:1 to oral doses of FIL 200 mg, FIL 100 mg, or placebo (PBO) once daily (QD) for 24 weeks; patients continued background therapy with conventional synthetic DMARDs. Results: Primary and all key secondary endpoints were met for both global (N=448, Genovese, 2018) and Japanese patient populations (n=40; FIL 200 mg, n=12; FIL 100 mg, n=15; and PBO, n=13). ACR20 response rates, HAQ-DI LS mean changes from baseline, and the percentage of Japanese patients with DAS28(CRP) ≤3.2 at week 12 are shown in Table 1 . In Japanese patients, treatment-emergent adverse event (AE) rates were similar for FIL 200 mg, FIL 100 mg, and PBO (75%, 60%, and 77%, respectively) and there were no serious AEs; there was 1 case of uncomplicated herpes zoster (FIL 200 mg); and no venous thrombotic events, opportunistic infection/active TB, malignancy, GI perforation, or death. Conclusion: In this phase 3 study in bDMARD-IR patients with active RA, treatment with FIL over a 24-week period was associated with significant improvements in signs and symptoms of RA, with a safety and efficacy profile in Japanese patients consistent with that in the global population. Thus, FIL may provide a novel treatment option for patients who continue to have active RA despite prior biologic therapy. References: [1] Genovese MC, et al. ACR 2018. Abstract L06. Disclosure of Interests: Tsutomu Takeuchi Grant/research support from: Astellas Pharma Inc, Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Takeda Pharmaceutical Co., Ltd., AbbVie GK, Asahikasei Pharma Corp., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Eisai Co., Ltd., AYUMI Pharmaceutical Corporation, Nipponkayaku Co. Ltd., Novartis Pharma K.K., Grant/research support from: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Grant/research support from: Astellas Pharma Inc., Bristol Myers Squibb, Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahi Kasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Janssen Pharmaceutical K.K., Celltrion Inc., Nipponkayaku Co. Ltd., and UCB Japan, Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., Abbivie GK, Nipponkayaku Co.Ltd, Janssen Pharmaceutical K.K., Astellas Pharma Inc., Taiho Pharmaceutical Co. Ltd., Chugai Pharmaceutical Co. Ltd., Taisho Toyama Pharmaceutical Co. Ltd., GlaxoSmithKline K.K., UCB Japan Co. Ltd., Consultant for: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., Asahi Kasei Medical K.K., AbbVie GK, Daiichi Sankyo Co., Ltd., Bristol Myers Squibb, and Nipponkayaku Co. Ltd., Speakers bureau: Astellas Pharma Inc., Bristol Myers Squibb, Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahi Kasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Janssen Pharmaceutical K.K., Celltrion Inc., Nipponkayaku Co. Ltd., and UCB Japan, Speakers bureau: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Speakers bureau: AbbVie GK., Bristol–Myers K.K., Chugai Pharmaceutical Co. Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Astellas Pharma Inc, Diaichi Sankyo Co. Ltd., Eisai Co. Ltd., Sanofi K.K., Teijin Pharma Ltd., Takeda Pharmaceutical Co. Ltd., Novartis Pharma K.K., Tsukasa Matsubara Consultant for: Nichi-Iko Pharmaceutical Co., Ltd, Pfizer Japan Inc., Speakers bureau: Astellas Pharma Inc, SEKISUI MEDICAL CO., LTD., UCB Japan Co. Ltd, DAIICHI SANKYO COMPANY Ltd, Bristol-Myers Squibb Company, ONO PHARMACEUTICAL CO., LTD., Mitsubishi Tanabe Pharma Corporation, Celltrion Healthcare Co., Ltd, AYUMI Pharmaceutical Corporation, Eisai Co., Ltd, Janssen Pharmaceutical K.K, Pfizer Japan Inc., Asahi Kasei Pharma Corporation, AbbVie GK., Chugai Pharmaceutical Co., Ltd, Eli Lilly Japan K.K., Tatsuya Atsumi Grant/research support from: Astellas Pharma Inc., Takeda Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Chugai Pharmaceutical Co., Ltd., Daiichi Sankyo Co. Ltd., Otsuka Pharmaceutical Co., Ltd. and Pfizer Inc. Alexion Inc., Bayer Yakuhin, Ltd, Otsuka Pharmaceutical Co., Ltd. Chugai Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Eisai Co., Ltd., Bristol-Myers Squibb Co., Daiichi Sankyo Co. Ltd., Mitsubishi Tanabe Pharma Co., Asahi Kasei Pharma Co., Consultant for: ONO PHARMACEUTICAL CO., LTD Sanofi K.K. Daiichi Sankyo Co., Ltd. Pfizer Inc., Speakers bureau: Mitsubishi Tanabe Pharma Co., Chugai Pharmaceutical Co., Ltd., Astellas Pharma Inc., Takeda Pharmaceutical Co., Ltd., Pfizer Inc., Daiichi Sankyo Co. Ltd., Bristol-Myers Squibb Co., Eli Lilly Japan K.K., Koichi Amano Grant/research support from: Asahi-Kasei Pharma, Speakers bureau: AbbVie GK, Chugai Pharmaceutical Co. Ltd, Eli Lilly, Pfizer Japan, Tanabe-Mitsubishi, Naoki Ishiguro Grant/research support from: AbbVie, Asahi Kasei, Astellas, Chugai, Daiichi-Sankyo, Eisai, Kaken, Mitsubishi Tanabe, Otsuka, Pfizer, Takeda, and Zimmer Biomet, Consultant for: Ono, Speakers bureau: Astellas, Bristol-Myers Squibb, Daiichi-Sankyo, Eli Lilly, Pfizer, and Taisho Toyama, Eiji Sugiyama Grant/research support from: AbbVie, Astellas, Ayumi, Bristol-Myers Squibb, Chugai, Eli Lilly, Pfizer, Sanofi, Takeda, Tanabe-Mitsubishi, Speakers bureau: AbbVie, Astellas, Ayumi, Bristol-Myers Squibb, Chugai, Eli Lilly, Kissei, Pfizer, Sanofi, Tanabe-Mitsubishi, Actelion, Kunihiro Yamaoka Grant/research support from: Mitsubishi-Tanabe Pharma, Eisai Pharma, Chugai Pharma, Glaxo Smith Kline, Asahikasei Pharma Corp., Ono Pharma, Consultant for: Mitsubishi-Tanabe Pharma, Eisai Pharma, Chugai Pharma, Glaxo Smith Kline, Asahikasei Pharma Corp., Ono Pharma, Speakers bureau: From: Pfizer, Chugai Pharma, Mitsubishi-Tanabe Pharma, Bristol-Myers Squibb, Takeda Industrial Pharma, GlaxoSmithKline, Nippon Shinyaku, Eli Lilly, Janssen Pharma, Eisai Pharma, Astellas Pharma, Actelion Pharmaceuticals, Otsuka Pharma, Ono Pharma, AbbVie, Mark C. Genovese Grant/research support from: Sanofi/Genzyme, Genentech/Roche, RPharm, Consultant for: Sanofi/Genzyme, Genentech/Roche, RPharm, Kenneth Kalunian Grant/research support from: Gilead Sciences, Inc., David Walker: None declared, Jacques-Eric Gottenberg Grant/research support from: Bristol-Myers Squibb, Grant/research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Lilly, Pfizer, Sanofi-Genzyme, UCB Pharma, Consultant for: Bristol-Myers Squibb, Eli Lilly, UCB, Sanofi-Genzyme, Pfizer, Kurt de Vlam Consultant for: Pfizer Inc, Consultant for: Johnson & Johnson, Neelufar Mozaffarian Shareholder of: Gilead, Employee of: Gilead, Beatrix Bartok Shareholder of: Gilead, Employee of: Gilead, Franziska Matzkies Shareholder of: Gilead, Employee of: Gilead, Jie Gao Shareholder of: Gilead, Employee of: Gilead, Ying Guo Shareholder of: Gilead, Employee of: Gilead, Chantal Tasset Shareholder of: Warrants from Galapagos, Employee of: Galapagos, John Sundy Shareholder of: Gilead Sciences, Inc., Employee of: Gilead Sciences, Inc., Yoshiya Tanaka Grant/research support from: Abbvie, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eisai, Mitsubishi-Tanabe, MSD, Ono, Taisho-Toyama, Takeda, Speakers bureau: Abbvie, Asahi-kasei, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eli Lilly, Eisai, Glaxo-Smithkline, Janssen, Mitsubishi-Tanabe, Novartis, Pfizer Japan Inc, Sanofi, Takeda, UCB, YL Biologics